The effectiveness promotional strategies of Nuri’s saving account-i / Mohd Izzuwan Abdul Razak - Abdul Razak, Mohd Izzuwan (Faculty of Business and Management, 2010)
The main objective of this research was to explore the effective Nuri’s saving accout-I promotional strategies towards non Malay. The other objective is to test the perception of non Malay towards Bank Rakyat and Nuri’s saving account-i. The respondents of this study were randomly selected from few locations in the Klang Valley. Filthy questionnaires had been distributed among those respondents. The researcher had used convenience sampling as the sampling technique. The questionnaire was designed to the selected respondents which they were asked varieties of questions regarding their perception to the Bank Rakyat Nuri’s saving account-i and promotional strategies. The process of analyzing and interpreting data has been presented with tables using methods such as frequency distribution and correlation.